Determinants of the high admission blood pressure in mild-to-moderate acute intracerebral hemorrhage. Issue 7 (July 2019) - Wang, Xia; Sandset, Else C.; Moullaali, Tom J.; Chen, Guojuan; Song, Lily; Carcel, Cheryl; Delcourt, Candice; Woodward, Mark; Robinson, Thompson; Chalmers, John; Arima, Hisatomi; Anderson, Craig S.
Abstract : Background and purpose: An early elevation in blood pressure (BP) is common after spontaneous intracerebral hemorrhage (ICH), has various potential causes, and is predictive of poor outcome. We aimed to determine the predictors of this phenomenon, in pooled analyses of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trials [INTERACT1 ( n = 404) and INTERACT2 ( n = 2829)]. Methods: INTERACT trials were international, open, blinded endpoint, randomized controlled trials of patients with spontaneous ICH (<6 h) and elevated SBP (150–220 mmHg) assigned to intensive (target SBP < 140 mmHg) or guideline-recommended (SBP < 180 mmHg) treatment. Multivariable linear and logistic regression models were used to determine associations between baseline variables and the high admission BP, with continuous and binary SBP measures, respectively. Results: Among 3233 patients (mean age 63 years; 37% female; baseline mean SBP 179 mmHg), both analytic approaches showed significant positive associations of high admission BP with history of hypertension, admission hyperglycemia at least 6.5 mmol/l, elevated heart rate, and greater neurological severity (National Institutes of Health Stroke Scale scores); and significant negative associations with prior use of antithrombotic agents and longer time from onset to randomization. Conclusion: The high admission BP of mild-to-moderate acute ICH is related to autonomic nervous system activated 'stress' rather than hematoma location and mass effect. Clinical trial registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00226096 and NCT00716079. Abstract : Supplemental Digital Content is available in the text